Analysis of Antioxidant Potential of Infusion from Variations in Particle Size of Cinnamon Leaves Simplicia (Cinnamomum burmannii) using the DPPH Method - Kasmadi, Fathnur Sani; Maulida, Dafa Riska; Jannah, Zahratul; Yuliawati, Yuliawati (Jurnal FARMASIMED (JFM), 2025)
Background: The Cinnamon plant is used as herbal therapy and spices for cooking food in Indonesia. The content of secondary metabolite compounds has the potential as an antioxidant. Variations in particle size have been proven to have the potential to attract compounds from herbal plants. Purpose: The research aimed to determine the antioxidant potential of cinnamon leaf infusion with different simplicia particle sizes. Method: The research method used in this research was the DPPH method, using Vitamin C as a comparison, and the concentration of simplicia used to make the infusion is 5%. Result: The test results showed that a 5% infusion of simplicia microparticles had higher antioxidants than simplicia infusion with an IC50 value of 74.89 ppm, which was included in the classification of strong antioxidant activity. In contrast, the IC50 value of simplicia infusion was 110.61 ppm, which was classified as moderate. Conclusion: The infusion of simplicia microparticles from cinnamon leaves can be developed as an alternative antioxidant from natural ingredients.